Unsteady shrinking sheet with mass transfer in a rotating fluid - Md. Ali, Fadzilah; Mohd Nazar, Roslinda; Md. Arifin, Norihan; Pop, Ioan (John Wiley & Sons, 2011)
In this paper, the problem of unsteady flow induced by a shrinking sheet with mass transfer in a rotating fluid is studied. The transformed boundary layer equations are solved numerically by an implicit finite‐difference scheme known as the Keller‐box method. The influence of rotation, unsteadiness and mass suction parameters on the reduced skin friction coefficients f ″(0) and g ′(0), as well as the lateral velocity and velocity profiles are presented and discussed in detail.